Preparation of microgel/sodium alginate composite granular hydrogels and their Cu2+ adsorption properties. Issue 102 (24th October 2016) - Zhao, Fang; Qin, Xuping; Feng, Shengyu
Abstract : Schematic diagram of microgel/SA composite spherical granular hydrogel formation. Abstract : Acrylamide/2-acrylamido-2-methylpropane sulfonic acid (AMPS)-based microgels containing hydroxymethyl groups and sodium alginate (SA) were used to prepare microgel/SA composite spherical granular hydrogels, which contained the SA network and a microgel network. Their preparation and Cu 2+ adsorption properties were investigated. Acetone was used as solvent for dehydration to remove some of the water before drying, which was important for the spherical morphology of dry granular hydrogels. The composite hydrogel had a comprehensive excellent performance. The Cu 2+ adsorption capacity decreased as the microgel/SA ratio increased, which was caused by the decrease of the ionic dominating adsorption groups. However, the composite hydrogel was stable in acid conditions without damage. The composite hydrogel had a faster swelling rate than that of the SA hydrogel. The low density and heterogeneous surface, such as micro cracks, micro particles and a large number of microgel particles with a diameter of about 100 nm, were conducive to increase the adsorption rate of the composite hydrogel. As the Cu 2+ concentration increased from 5 to 35 mmol L −1, the Cu 2+ adsorption capacity of the composite hydrogels with a microgel/SA mass ratio of 2.4 increased from 0.11 to 0.73 mmol g −1 . The Langmuir and Freundlich isotherm adsorption equations were used to fit the adsorption of the microgel/SA hydrogel with different Cu 2+ concentrations. The fitting results showed that the Freundlich isotherm equation had a good fitting effect. The pH value of Cu 2+ solutions also affects the adsorption capacity. The hydrogel also has the ability to adsorb other metal ions.